Ocular cysticercosis in pediatric patient - Mateo Gasca-Sánchez; Daniela Jaramillo; Nathalia Pachón-Blanco; Natalia Marín-Núñez; Tatiana Urrea-Victoria (Revista Brasileira de Oftalmologia, 2023)
ABSTRACT Ocular cysticercosis is a parasitic infection caused by Taenia solium. Its early diagnosis and treatment decreases the possibility of visual morbidity. It can either compromise the anterior chamber or the posterior segment, which translates into an very variable and interspecific presentation that changes depending on the site of the infection. It is important to report this case due to its low presentation rate and the fact that a high suspicion index is required to make an assertive and timely diagnosis. This is especially important in geographical areas that are endemic to this parasite due to the direct relationship between an early diagnosis and treatment and better visual outcomes. In this case report, we will discuss the multidisciplinary interventions of a pediatric patient in a high complexity hospital.